The Sandor-Smarandache function with a prime factor (Journal of Bangladesh Academy of Sciences, 2022)
The Sandor-Smarandache function, denoted by SS(n), is a newly-introduced Smarandache-type arithmetic function. This paper focuses on the functions SS(30p), SS(60p), SS(210p), SS(420p) and SS(840p), where p ( ≥2) is a prime. At the end of the paper, four tables, giving the values of SS(30p), SS(60p), SS(210p) and SS(420p) for the first 200 primes, calculated on a computer, are given.J. Bangladesh Acad. Sci. 46(1); 65-73: June 2022